Mutual Prodrugs of 5‐Fluorouracil: From a Classic Chemotherapeutic Agent to Novel Potential Anticancer Drugs. (7th September 2021) - Ciaffaglione, Valeria; Modica, Maria N.; Pittalà, Valeria; Romeo, Giuseppe; Salerno, Loredana; Intagliata, Sebastiano
Abstract: The development of potent antitumor agents with a low toxicological profile against healthy cells is still one of the greatest challenges facing medicinal chemistry. In this context, the "mutual prodrug" approach has emerged as a potential tool to overcome undesirable physicochemical features and mitigate the side effects of approved drugs. Among broad‐spectrum chemotherapeutics available for clinical use today, 5‐fluorouracil (5‐FU) is one of the most representative, also included in the World Health Organization model list of essential medicines. Unfortunately, severe side effects and drug resistance phenomena are still the primary limits and drawbacks in its clinical use. This review describes the progress made over the last ten years in developing 5‐FU‐based mutual prodrugs to improve the therapeutic profile and achieve targeted delivery to cancer tissues. Abstract : New and improved : 5‐Fluorouracil (5‐FU) is one of the most commonly used chemotherapeutic agents; however, its use is limited by unfavorable physicochemical properties and high nonspecific cytotoxic effects. Therefore, to overcome specific drawbacks of 5‐FU and to enhance its therapeutic efficacy, several 5‐FU‐based mutual prodrugs have been developed in recent years for both improving biological activity and achieving targeted delivery to cancer tissues.